Pengaruh Penggunaan Media Sosial terhadap Kejahatan Anak - Setiawati, Vera (Universitas Muhammadiyah Yogyakarta, 2025)
The rapid advancement of technology demands individuals to continuously adapt and take greater responsibility. This is particularly evident in the growing dependence of society—including children—on technology and social media. Such dependency highlights the profound role that technology plays in daily life. While technological progress offers numerous benefits, it also brings significant challenges, especially in the context of children's education and behavior. The study aims to examine and analyze the regulation of social media use in relation to the rise of juvenile delinquency. The research is guided by two central questions: (1) What is the impact of social media use on juvenile crime? and (2) To what extent is juvenile crime influenced by social media? Using a normative juridical approach, the findings indicate that social media can have both positive and negative impacts on children. In particular, the negative influence often manifests in behavioral issues, such as disobedience or deviant conduct, with children frequently exhibiting defiant attitudes and influencing their peers to engage in similar behaviors or fulfill their demands. These outcomes underscore the need for more comprehensive regulation and educational strategies to mitigate the adverse effects of social media on youth.